Cultivated gingers of peninsular Malaysia: ultilization profiles and micropropagation - Ibrahim, H.; Khalid, Norzulaani; Hussin, K. (Singapore Botanic Gardens, 2007)
There are approximately 160 species of Zingiberaceae belonging to 18 genera in Peninsular Malaysia. Roughly 16-20 are traditionally utilized by the indigenous folks as spices, condiments, vegetables, food flavours and medicines. The resurgence of interest in herbs and potential lucrative anticipated revenues from the herbal industry have spurred renewed interest in exploiting traditional knowledge and practices into scientific realities. Current research priorities offer promising developed of natural resources into neutraceuticals, cosmeceuticals and biopharmaceuticals. Hence the need to profile of fingerprint species for quality control and consistency of the species utilized. It is also important to establish protocols for micropropagation as a means of providing consistent supply of stable and elite materials for mass propagation and commercialization. Selected examples of indigenous uses, species profiles and successful micropropagation of cultivated gingers are discussed.